Analysis of acute myeloid leukemia incidence and geographic distribution in Canada from 1992 to 2010 reveals disease clusters in Sarnia and other industrial US border cities in Ontario. Issue 11 (27th February 2019) - Ghazawi, Feras M.; Le, Michelle; Cyr, Janelle; Netchiporouk, Elena; Rahme, Elham; Alakel, Akram; Zubarev, Andrei; Powell, Mathieu; Moreau, Linda; Roshdy, Osama; Glassman, Steven J.; Sasseville, Denis; et al.
Abstract : Background: Several risk factors have been implicated in acute myeloid leukemia (AML) leukemogenesis. However, the epidemiologic distribution and precise triggers for AML in Canada remain poorly understood. Methods: In this study, demographic data for AML patients in Canada from 1992 to 2010 were analyzed using 3 independent population‐based cancer registries. The AML incidence and mortality rates were examined at the levels of province/territory, city, and forward sortation area (FSA) postal code. Results: In total, 18, 085 patients were identified. AML incidence was documented to be 30.61 cases per million individuals per year (95% confidence interval [CI], 30.17‐31.06) from 1992 to 2010. Five industrial cities in Ontario were identified where incidence rates were significantly higher than the national average: Sarnia, Sault Ste. Marie, Thunder Bay, St. Catharines, and Hamilton. Analysis at the FSA postal code level identified significant patient clusters of AML in these cities. Specifically, FSA N7V in Sarnia, Ontario had an incidence of 106.81 (95% CI, 70.96‐161.86) cases per million individuals per year, which is >3 times higher than the national average. The pollution from local oil refineries and chemical plants in Sarnia may be implicated as a risk factor for AML in that city. Analysis of mortality rates at the province and city levels corroborated the findings from the incidence data. Conclusion: These results provide a comprehensive analysis of AML burden in Canada and reveal striking geographic case clustering in industrial Ontario cities and potentially implicate exposure to materials/pollution from these plants as an important risk factor for developing AML in Canada. Abstract : There is limited knowledge on the epidemiology and geographic distribution of acute myeloid leukemia (AML) in Canada. Exposure to materials/pollution from oil refineries and chemical plants are important risk factors for developing AML in Canada.